Effectiveness of soft robotic glove versus repetitive transcranial magnetic stimulation in post-stroke patients with severe upper limb dysfunction: A randomised controlled trial - Wang, Taotao; Liu, Zhonghua; Gu, Jianxiong; Tan, Jizhi; Hu, Tian (Frontiers in Neurology, 2023)
ABSTRACT Purpose: To explore the difference in the rehabilitation effect between soft robotic gloves and repetitive transcranial magnetic stimulation for patients with severe upper limb motor dysfunction after stroke. Methods: 69 post-stroke patients with severe upper limb dysfunction were randomly assigned to the repetitive transcranial magnetic group, the soft robotic glove group, and the conventional treatment group. The primary outcomes were Fugl-Meyer upper limb Motor Assessment (FMA-UE) and Modified Barthel Index (MBI). The secondary endpoint was the amplitude surface electromyogram of extensor wrist muscle (sEMG) and cerebral hemispheric resting motor threshold (RMT). Results: The change of FMA-UE score in the soft machine glove group was better than that in the conventional treatment group ( median difference: 2 points; 95 % confidence interval [ 1,3] ), the difference was statistically significant ( P＜0.05 ) ; and there was no significant difference with the repetitive transcranial magnetic stimulation group ( median difference: 0 points; 95 % confidence interval [ -1,2 ]；P（0.547）> 0.05 ). There was no significant difference in the change of MBI score between the soft machine glove group and the conventional treatment group and the repetitive transcranial magnetic treatment group (F= 2.458, P（0.093）> 0.05). There was no significant difference in the change of sEMG score between the soft robotic glove group and the conventional treatment group and the repetitive transcranial magnetic treatment group ( H=0.042, P（0.980）> 0.05). The change of RMT score in the soft machine glove group was inferior to that in the repetitive transcranial magnetic treatment group ( difference: -1.09; 95 % confidence interval [ -2.048,0.048 ] ), the difference was statistically significant ( P＜0.05 ); and there was no significant difference between the conventional treatment group (difference: 0.31points; 95 % confidence interval [ -0.879,0.358 ] ; P（0.495）> 0.05 ). Conclusion: For patients with severe dyskinesia after stroke, soft mechanical gloves are as effective as repetitive transcranial magnetic stimulation . In addition, conventional treatment combined with repetitive transcranial magnetic stimulation (rTMS) or soft robotic glove produced better rehabilitation outcomes than conventional treatment alone. Keywords: repetitive transcranial magnetic stimulation; soft robotic glove; Motor dysfunction after stroke;